A case of adult intussusception with greyscale, contrast-enhanced ultrasound and computerised tomography correlation. (May 2017) - Rafailidis, Vasileios; Phillips, Claudette; Yusuf, Gibran; Sidhu, Paul
Intussusception is often misdiagnosed as a cause of bowel ischemia and obstruction among adults due to its relatively rare presentation outside of the paediatric population. Ultrasound is often the first-line investigation for non-specific abdominal pain and can identify the presence of intussusception. In the adult population, it is essential to evaluate for causes and consequences of intussusception; as a result, computerised tomography is often deemed necessary. However, contrast-enhanced ultrasound allows for evaluation of potential causes and complications, including a neoplastic lead point and ischaemia of the bowel, whilst avoiding ionising radiation or nephrotoxic iodinated contrast. We report a case of adult intussusception with a polyp lead point with ultrasound, contrast-enhanced ultrasound and computerised tomography correlation.